The burning bush : writings on Jews and Judaism - Solovyov, Vladimir Sergeyevich, 1853-1900 (University of Notre Dame Press, 2016)
"In The Burning Bush, Glazov conducts a profoundly original inquiry into Vladimir Solovyov's attitude toward Judaism. Solovyov (1853-1900) was one of the most remarkable figures of the 19th century: He was the most important Russian speculative thinker of that century, publishing major works on theoretical philosophy, the philosophy of religion, and ethics; he also produced sensitive literary criticism and incisive essays on current political, social, and ecclesiastical questions. The eminent theologian Hans Urs von Balthasar designated Solovyov as the greatest artist of conceptual order and organization--after Thomas Aquinas--in the entire history of thought, a thinker who borrows from all systems after purging them of their negations. Solovyov was also the first major Russian thinker to enter into ecumenical dialogue with Jewish scholars and theologians, and Glazov's main concern is (1) to translate as completely as possible all of Solovyov's writings on Judaism and to annotate these texts by identifying persons, places, and citations, especially in the Biblical and rabbinic literature; and (2) to synthesize the information gleaned from these writings with key recollections of Solovyov's attitudes toward Jews and Judaism by his immediate family, friends, and early biographers. Glazov collects, translates, and comments on all the relevant primary texts: writings, letters, pamphlets, protests, political documents, and prayers which relate to Solovyov's work on Jewish matters:--